2014
DOI: 10.1111/vox.12215
|View full text |Cite
|
Sign up to set email alerts
|

Febrile non‐haemolytic transfusion reaction occurrence and potential risk factors among the U.S. elderly transfused in the inpatient setting, as recorded in Medicare databases during 2011–2012

Abstract: Our study shows increased FNHTR occurrence among elderly with greater number of units and with RBCs- and platelets-containing transfusions, suggesting need to evaluate effectiveness of prestorage leucoreduction in elderly. The study also suggests importance of prior recipient alloimmunization and underlying health conditions in the development of FNHTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
2
17
2
1
Order By: Relevance
“…In general, rates of FNHTR were lower in leucoreduced versus non‐leucoreduced products within the same population (Table ) . With prospective surveillance, the pooled rate of FNHTR was 1191/100 000 units or one in every 84 units; this compares with one case in 3885 RBC units from haemovigilance.…”
Section: Resultsmentioning
confidence: 96%
“…In general, rates of FNHTR were lower in leucoreduced versus non‐leucoreduced products within the same population (Table ) . With prospective surveillance, the pooled rate of FNHTR was 1191/100 000 units or one in every 84 units; this compares with one case in 3885 RBC units from haemovigilance.…”
Section: Resultsmentioning
confidence: 96%
“…Nonetheless, FNHTRs caused by RBC were likely to appear after the first transfusion . Another report indicated that the incidence of FNHTRs increased as the frequency of transfusions increased . Therefore, controversy regarding FNHTRs still exists.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that Menis et al . observed in their study that the incidence of FNHTR decreased with age (48·2 per 100 000 stays in patients aged 85 years or over versus 63·8 per 100 000 stays in patients aged 65–69 years).…”
Section: Discussionmentioning
confidence: 87%